2013
DOI: 10.3109/13668250.2013.828833
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary development in children with Down syndrome: Longitudinal and cross-sectional data

Abstract: Although there are similarities with vocabulary growth in typically developing children, lexical development in children with Down syndrome appears to lag behind their cognitive development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 21 publications
3
24
1
6
Order By: Relevance
“…The delay in the development of communicative skills in individuals with DS is foreseen in the literature 7,10,13,19,20,24,25 , even though these individuals do not behave in a homogenous way 10,24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The delay in the development of communicative skills in individuals with DS is foreseen in the literature 7,10,13,19,20,24,25 , even though these individuals do not behave in a homogenous way 10,24 .…”
Section: Resultsmentioning
confidence: 99%
“…Authors have shown the lexical acquisition, although delayed, follows the same development route 24 . Other studies 6,10,13,[23][24][25] also pointed out the need to verify receptive and expressive skills that can be more limited in DS individuals. To compensate their oral production delay, many children use sign language for longer periods, aiming to improve their interlocutor comprehension 13,[19][20][21]23,26 .…”
Section: Characterization Of the Casuistrymentioning
confidence: 99%
See 1 more Smart Citation
“…This condition is usually associated with psychomotor delays and cognitive impairments. Moreover, the language development of children with Down syndrome is usually particularly impaired (Abbeduto et al 2007;Zampini & D'Odorico 2013), and the discrepancy between language comprehension and production is wider than in typically developing children (Caselli et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent longitudinal study of lexical development in children with DS analyzed the developmental trend of vocabulary acquisition in a group of 18 Italian children (Zampini & D'Odorico, 2013). A sample of 10 2-year-old children with DS was followed until they were 3 years of age, and 8 3-year-old children were followed until they were 4 years.…”
Section: Down Syndromementioning
confidence: 99%